Markets and Jungles - Thomas Gall; Paolo Masella (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Economic institutions determine prospects for growth and development. This paper examines necessary conditions for an economy to support institutions that implement markets. Agents differ in land holdings, skill, and power. A competitive market assigns land to the skilled, not necessarily to the powerful. Therefore a market allocation needs to be robust to coalitional expropriation. In a dynamic setting, market payoffs may induce sufficient inequality in next period's endowments for markets to alternate with expropriation in a limit cycle, decreasing efficiency and amplifying macroeconomic fluctuations. Long run stability of markets is favored by higher social mobility, more initial equality, and less mismatch between demand and supply.
Keywords: E02; O43; C71; 330; Expropriation; market institutions; inequality; fluctuations; coalition formation